Advanced characterisation of bituminous sub-ballast for its application in railway tracks: The influence of temperature. (30th December 2015) - Sol-Sánchez, M.; Pirozzolo, L.; Moreno-Navarro, F.; Rubio-Gámez, M.C.
Graphical abstract: Highlights: Bituminous sub-ballast has been characterised under service life temperature. A full scale test evaluated the sub-ballast under different load conditions. Bituminous sub-ballast improves the mechanical response of the track. Bituminous sub-ballast exhibits higher strength against the trains loads. Abstract: The use of bituminous sub-ballast in railway tracks is regarded as an appropriate solution for improving the strength of the section. However, for its widespread application, more in-depth studies are needed to assess its efficacy with respect to the main requirements that this material must meet under various service conditions. Such conditions include the range of temperatures that can occur during the service life of the railway tracks, which can modify the behaviour of bituminous material. This paper therefore focuses on evaluating the mechanical behaviour of bituminous material (under both routine and adverse temperatures that are expected in railway lines in extreme climates) in comparison to that presented by conventional granular sub-ballast. In particular, performance is examined with respect to the main requirements that need to be met by these materials (resistance to plastic and punching deformations, bearing capacity, stress dissipation, cracking resistance, and waterproof properties) for their use in railway tracks. At the same time, their influence on the performance of the global section was assessed for both types of sub-ballast by means of a full-scale test. The results demonstrated that the use of bituminous sub-ballast could improve both the mechanical response of the track and the protection of the remainder of the track bed layers, since this material exhibited higher strength against the loads imposed by passing trains, lower permeability, and a higher capacity to dissipate stresses transmitted by the ballast to the substructure. However, it is also important to consider that temperature plays a fundamental role in the resistance of bituminous sub-ballast to plastic and punching deformations, whilst its resistance to cracking declines sharply at higher temperatures. This could limit its application in railway lines in regions where values of this parameter are expected to be higher than those commonly recorded for this layer.